Semi-Industrial Fluorination of β-Keto Esters with SF4: Safety vs Efficacy - Trofymchuk, Serhii A.; Kliukovskyi, Denys V.; Semenov, Sergey V.; Khairulin, Andrii R.; Shevchenko, Valerii O.; Bugera, Maksym Y.; Tarasenko, Karen V.; Volochnyuk, Dmitriy M.; Ryabukhin, Sergey V. (Synlett, 2020)
The possibility of deoxofluorination of β-keto esters using SF4 was investigated. The scope and limitation of the reaction were determined. The efficient method for the synthesis of β,β-difluorocarboxylic acids was elaborated based on the reaction. The set of mentioned acids, being the perspective building blocks for medicinal chemistry, were synthesized on multigram scale. The safety of SF4 use was discussed. The described method does not improve upon the safety of using SF4, but practical recommendations for working with the reagent are proposed. Despite the hazards of using toxic SF4, a significant increase of efficacy in the synthesis of medicinal-chemistry-relevant building blocks, based on the reaction, in comparison with earlier described approaches is shown.
Keywords: organofluorine compounds; deoxofluorination; sulfur tetrafluoride; β-keto esters; β,β-difluorocarboxylic acids; building blocks